KEPUASAN KERJA DENGAN KOMITMEN ORGANISASI PADA PEMADAM KEBAKARAN DI KABUPATEN SIDOARJO - Erina Dwi Agustin; Nilna Muna Sholihah; Sinta Ayu Ardiana; Sultan Fadillah Ardiansyah; Soffy Balgies (Universitas Bina Taruna Gorontalo, 2022)
The purpose of this research is to know how to relate job satisfaction with the organization's commitment to firefighters in sidoarjo district. This kind of research USES quantitative research. Hypothetical testing. This research sample is sidoarjo county PMK with a total of 78 samples. Data processing is done using version 25 of the SPSS device. Research shows that working satisfaction in the NCG region's ncd-d-2 region is low, sufficient, and high, where most of the work satisfaction of the respondents is low enough (70%), while the high work satisfaction alone is 13 (17%) and the low job satisfaction of 10 respondents (13%). However, the rupiah still had a chance to strengthen to rp9,100 per dollar, he said.